Relationship maximal and explosive power to performance of motor actions in weightlifting - Sivokhin, I.; Fyodorov, A.; Tapsir, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Identification of the most informative indicators of special physical fitness of athletes, as well as the assessment of their impact on the realizable efficiency of motor actions allows to obtain objective data for the development of more effective models of training and improvement of quality control by correcting the direction, structure and content of the training sessions. The purpose of research - to investigate the relationship of maximal and explosive power and performance of motor actions in weightlifting. Methods: The study took part lifters of high qualification, aged 20-23 years (n=10). To determine the explosive power, which was estimated by the duration of the flight phase in the jumping tests, we use tensometric platform. Jumping carried out with a stop and with fast switching in the legs by bending at the extension. Jumps were performed with a barbell on your shoulders and weighing 50 and 100 kg and without complications. To determine the maximum strength applied squats on his shoulders with a maximum weight. Using test determined the maximum result in the snatch. Results: The result in the snatch is a high degree of relationship with maximum strength (r=0.85). In addition to the high significance of the maximum strength to result in the snatch, an essential feature is the explosive power. Analysis of the relationship results in the snatch and jumping tests indicate that the greatest values coefficients of correlation are the results of such tests, like jumping up without burdening with fast switching in the muscles of the lower extremities with inferior mode to overcoming (r=0.80). Through the use of regression analysis of the parameters studied found that with an increase in the squat result (the maximum strength) of 10 kg in the snatch result increases by an average of 5.2 kg, and the increase of the flight phase jump time 10 ms increases to result in the snatch 18.3 kg. Discussion / Conclusion: It is found that the tightness of relationship of results in the snatch, squats and squat jumps, at their joint effect is increased (r=0.87), and determines the result to sports 76.0%, and 50.0% is necessary to share the maximum power while the share of explosive power of 26.0%. Results in jumping to the stop and fast switching leg from bending at the extension at their joint effect, a high degree of correlation with the result in snatch (r=0.85) and its variation is determined at 72.0%. The share of jumps with a stop there are only 7.0%, while the share of jumps with fast switching in the muscles necessary to 65.0%. This confirms the importance of the use of stored elastic energy of the working muscles during rapid switching cycle «tension - reducing».